Teaching skills to resolve conflicts with aggressive patients in nursing through the Case Method (MoC) - Marta Arrue Mauleon (Universitat Politècnica de València, 2013)
This paper seeks to design a teaching sequence that provides students with an opportunity to acquire knowledge, skills, attitudes and values needed when dealing with an aggressive patient. To design the teaching method, a strategy of active teaching, and in particular the so-called Case Method, has been chosen. The preparation of the case occurred during the 2010-11 academic year and its implementation took place in 2011-2012 during a course called "Relationship and Communication for Nursing Care". The participants were 2nd year nursing students at the Basque Country University. The results of implementation show that the MoC is a satisfactory tool for the acquisition of the proposed competences, as well as being a learning method that is very well received by students in general. On completion, 97.1% of the participants said they would repeat this methodology and 100% said that "this methodology has proven helpful or very helpful to me in comparison with the classic expositive methodology." In addition, all students have passed at least the minimum of the required learning outcome. The proposed experience should be an incentive to continue to expand the range of possibilities offered by active methods.